Format Program Siaran Radio Dangdut Jakarta dalam Konsultasi Keluarga dan Dakwah - Arbi, Armawati (Jurnal Komunikasi Islam, 2012)
The terms of the format has often been misinterpreted in several Islamic Communication and Broadcast (KPI) students’ thesis, State Islamic University (UIN) Syarif Hidayatullah, Jakarta. This article examines the implementation of the program format of the broadcast on five dangdut radio in Jakarta. The format of the radio station programs is trying to satisfy the needs of the listeners. The listeners are very interested when radio format meet their needs and satisfaction. The results of this study present a pattern of five radio formats. Each radio has its own identity and branded name through its format.Keywords: broadcast format, proselytizing program, family consultation, dangdut radio---------------------------------------------------------------------------Istilah tentang format, sering disalahartikan dalam beberapa skripsi mahasiswa KPI Universitas Islam Negeri (UIN) Jakarta. Artikel ini mengkaji lebih jauh pelaksanaan tentang format program dari siaran pada lima radio Dangdut Jakarta. Format program stasiun radio berusaha memuaskan kebutuhan pendengar. Pendengar sangat tertarik bila format radio menyediakan kebutuhan dan memenuhi kepuasannya. Hasil penelitian ini menyajikan corak lima format radio. Masing-masing radio memiliki identitas dan nama mereknya melalui formatnya.Kata kunci: format siaran, program dakwah, konsultasi keluarga, radio dangdut